(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the questions of describing the field structure of politeness in speech etiquette. The study of politeness in modern linguistics is carried out in the framework of anthropological, ethnolinguistic, pragmatic, sociopsycholinguistic works. Different approaches explore politeness in language theory and practice, in relation to the normative framework of behavior, cultural-specific factors and the situation factor.